Modelling Estimation of the Available Rainwater Resource in Gbédji-Kotovi Clay Area for Supplying Dikes and Dams - Mounou Sambieni, Kassa Issifou; Codo, Francois de Paule (My University, 2020)
Floods and flows data are useful for dimensioning of dikes and dams which often include evacuation devices that regulate flows to ensure the volumes of water. The objective of this study is to estimate the available water resource in the village of Gbédji-Kotovi, located in the watershed of Couffo river in Benin by using sequentially, the HBV (Hydrologiska Byråns Vattenbalansavdelning) and GR4J (Rural Engineering model with 4 daily parameters) climate models. Hydrographs of water levels are simulated according to the calibration period (1994-1999) different from the validation one (1982-1988). Considering the Nash-Sutcliffe model Efficiency coefficient (NSE), the performance of GR4J model during calibration is slightly higher than the performance of the HBV model, while during the validation, the contrary is noticed. The annual rain- fall average simulated is 1117.7 mm/year while the average observed is 1104.6 mm/year over the period 1981-2005. By 2050, on one hand, the annual flow rate values will vary from −19.2 to −11.9%, while the actual evapotranspiration will vary between 0.5 and −5.8; on another hand, the potential evapotranspira- tion and the annual precipitation remain constant. An average flow of 187 mil- lions m 3 /year for annual average water depth of 1094 mm is obtained at Lanta rain station, which covers an area of 1664.47 km 2 , while this flow enabled an average flow of 327.5 millons m 3 /year to be obtained at the virtual station of our study area of 2908.15 km 2 . The flow rates corresponding to the return pe- riods of 10, 25 and 50 years vary from 5.51 to 12.67 m 3 /s at the outlet of the virtual station; while those at the outlet of Lanta station vary from 3.6 to 6.6 m 3 /s. However, the simulated water quantiles cannot be fully mobilized; be- cause of the uses, they undergo upstream and downstream. Thus, Gbédji-Kotovi locality requires the implementation of an integrated water resource man- agement strategy that includes the construction of dikes and dams.
Keywords: Rainwater; Modelling; Couffo Watershed; Gbédji-Kotovi; Dikes and Dams